Surgical Treatment of Congenital Meningocele in A Calf - Kom, Mustafa; Karabulut, Enis; Han, M. Cengiz; Ceribasi, Ali Osman (Kafkas Univ, Veteriner Fakultesi Dergisi, 2009)
The material of this study was consisted of three days old, male Holstein calf that presented to Firat University Veterinary Faculty Department of Surgery with complaint a mass in the occipital region of cranium and no stand up. General examination of calf was observed 9 x 17 cm dimensions a fluctuated mass in the occipital region. Laterolateral radiography of the cranium was determined foramen 4 cm diameter at the os occipitalis and become full with fluid of sac. The mass extirpated with surgical excision. The operation later was applied parenteral Seftriakson (Unacefin, Fako) for ten days. The operation later computed tomography (CT) of the cranium was scanned. One days after the operation, the animal was able to stand up and suck. But was noticed discordant in walking of animal. Ten days after the operation the calf completely improved. During two year of following up period, no complication was determined.
Bir buza?ıda konjenital meningosel olgusunun cerrahi sa?altımı
Keywords: Calf; Congenital meningocele; Treatment